Utilization of health services for skin disorders during military operations. A population- based study - Amir Horev; Shanny Edan-Reuven; Ron Eshel; Lena Novack (PAGEPress Publications, 2020)
In addition to the immediate casualties of armed conflicts, their indirect impact may bring even more damage by causing malfunctioning of health systems and impaired access to diagnosis and treatment. We conducted a population-based study, to assess the utilization rates of health services due to skin disorders, among civilians exposed to missile attacks and siren alarms during three military operations in Israel. The study was designed as a natural experiment, whereas periods of military operations were compared to the non-military times. During the military operations, when sirens and missiles were an everyday experience, the number of visits to dermatologists was 1.07-1.16 times lower [Relative Risk (RR)=0.86-0.92] as compared to the non-military periods, especially evident for patients residing closer to the military zone, where it dropped almost 2- folds (RR=0.52). Although perceived nonurgent in their majority, the routine care should not be delayed to prevent more serious skin conditions.